PENDIDIKAN KARAKTER BERBASIS MULTIKULTURAL: STRATEGI MEMBANGUN KESETARAAN DI SEKOLAH SECARA INKLUSIF DAN BERKEADILAN - T, Marlini; BJ, Jusmiwarti; Julhadi, Julhadi (STKIP Pesisir Selatan, 2025)
Indonesia, as a nation based on Pancasila, upholds ethical values, morals, and human rights, maintains harmony among its citizens, fosters cooperation, and respects differences, symbols, religion, race, skin color, and so on. This country is incredibly rich in cultural, religious, ethnic, and linguistic diversity. Amidst this reality, schools serve as a strategic space for fostering mutual respect, tolerance, and a sense of community. However, educational practices often do not fully reflect the values ​​of equality and justice due to persistent stereotypes, cultural bias, and unequal access. This paper aims to explain the concept of multicultural-based character education and its implementation strategies for building inclusive and equitable schools. The writing method uses a library research approach through a review of relevant theories and literature. The study results indicate that multicultural-based character education can be implemented through curriculum integration, dialogic learning strategies, an inclusive school culture, and partnerships between schools, families, and the community. With the right strategies, schools can become safe and equitable spaces for all students without discrimination.